2019
DOI: 10.3390/app9050913
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Natural Bonding Strength between Stay-In-Place Form and Concrete in FRP-Concrete Decks/Beams

Abstract: The Fiber Reinforced Polymer (FRP)-concrete hybrid deck/beam is a structural system that combines the durable thin-walled FRP composite profiles and the cost-effective concrete by interfacial shear connections. The interfacial slip can reduce the composite action, thereby causing a degradation of flexural rigidity and capacity. Therefore, using stay-in-place (SIP) forms is a simple way to fully utilize the natural bonding between FRP and concrete, which plays a pivotal role in the structural design of FRP-conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The shape of those load–slip curves has some similarity to that of the A-IM samples. It is also interesting to note that Gong et al [ 43 ] observed progressive failure before the bearing stage, due to the loss of the natural bond when using stay-in-place forms (SIP), and they achieved curves similar to those of samples AS-M. Later, when bolts bore loads, the performance was totally different from that of our samples.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The shape of those load–slip curves has some similarity to that of the A-IM samples. It is also interesting to note that Gong et al [ 43 ] observed progressive failure before the bearing stage, due to the loss of the natural bond when using stay-in-place forms (SIP), and they achieved curves similar to those of samples AS-M. Later, when bolts bore loads, the performance was totally different from that of our samples.…”
Section: Resultsmentioning
confidence: 55%
“…Gong et al [ 42 ] studied the interfacial stress in FRP–concrete hybrid beams using the finite difference method (FDM) and push-out tests. Moreover, Gong et al [ 43 ] performed an experimental investigation of the natural bonding between FRP and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Gong et al conducted an experimental investigation of the natural bonding strength between FRP profiles and in situ cast concrete [64]. Four pushout test specimens were carried out as same as the part of [63], in which two specimens were equipped with steel bolts as the interfacial connection, and the other two were equipped with the SIP form and steel bolts together.…”
Section: Experimental Validation By the Pushout Testmentioning
confidence: 99%
“…These artificial or natural phenomena cause devastating consequences because the deficiency of RC structures. Using Fiber Reinforced Polymer (FRP) is one of the most common methods of retrofitting RC members (Gong et al, 2019;Qin et al, 2019;Soleimani and Sayyar Roudsari, 2019). It can be used to enhance not only capability of RC structure for seismic loads but also, employing FRP material is suitable for extreme loading conditions.…”
Section: Introductionmentioning
confidence: 99%